Omfattningen av icke avverkade områden i samband med slutavverkning - Andersson, Peter (SLU/Dept. of Forest Products, 2003)
This final thesis is performed on commission of Torsby forestry administration, Stora Enso Skog. Stora Enso Skog is one of the major forestry companies of Sweden. The main business area is located in and around the region of Bergslagen.